ANALISIS FRAMING BERITA KASUS AHOK DALAM POLEMIK SURAT AL-MAIDAH 51 PADA KOMPAS.COM DAN REPUBLIKA.CO.ID - Didik Hariyanto (Universitas Muhammadiyah Jember, 2018)
This study aims to determine the construction of the media on Ahok's preaching in the polemic on Al-Maidah 51 (analysis of framing on kompas.com and republika.co.id edition 27 September - 27 December 2016). The research method used is a qualitative research method framing analysis of Zhongdang Pan and Gerald M. Kosicki models. The results of the framing analysis of Ahok in Polemik Surat Al-Maidah 51 that, news articles published by the two online news portals are not neutral. Kompas.com, looks very strongly in defense of Ahok, while Republika.co.id looks very strongly in defense of Muslims. Group affiliation and interest sentiment are very influential in this news. This can be seen from the analysis using the agenda theory setting which greatly affects the Kompas.com and Republika.co.id online media in the selection of newsKeywords: Framing analysis, media construction, agenda setting, Al-Maidah-51